The Impact of Financial Statement Fraud on Bankruptcy Banking Companies in Indonesia - Orien Sriminingsih; Isnawati Isnawati (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Financial statement fraud is a form of fraud that is often carried out by companies which involves the deliberate presentation of financial information so that users of financial statements are deceived. The aim of this research is to determine the effect of financial statement fraud on bankruptcy in banking companies in Indonesia, especially the People's Economic Bank. The research uses data originating from People's Economic Bank publication reports published on the official Financial Services Authorization website. The data used in this research is secondary data consisting of financial reports from 30 BPRs that are still active and financial reports from 30 BPRs that have gone bankrupt. The analysis was carried out using the different test analysis method using SPSS 23. The results of this research indicate that financial statement fraud has no influence on bankruptcy.